PN-Doped tetraphenylnaphthalene: a straightforward synthetic strategy analogous to BN-annulation. Issue 91 (2nd November 2021) - Park, Jupil; Kim, So Jung; Kwon, Hansol; Jin, Eunji; Yoon, Kihwan; Kim, HyunHo; Shadman, Sahar; Choe, Wonyoung; Kim, Joonghan; Park, Young S.
Abstract : Installation of a PN bond in π-systems. Abstract : Compared to BN heterocycles, few studies on PN heterocycles have been reported to date. Herein, we developed an efficient synthetic strategy analogous to BN-annulation to simultaneously incorporate a PN bond and a halogen group into the naphthalene core. Subsequently, we prepared PN-containing tetraphenylnaphthalene using this method, followed by palladium-catalyzed cross-coupling and reduction reactions. The prepared molecule was characterized via X-ray crystallography, NMR spectroscopy, UV-vis spectroscopy, and cyclic voltammetry.